Urgensi Pendidikan Pemilih Berkelanjutan Pasca Tahapan Pemilihan Umum 2024 Oleh KPU Kota Balikpapan - Muhammad Randy Pratama Lubis; Mutia Permata Putri; Insan Tajali Nur (Pusat Riset dan Inovasi Nasional, 2026)
For the general public, Indonesia’s five-year electoral cycle is often perceived merely as a procedural voting event, overlooking the substance and quality of how voters select presidential or regional leaders. Following the 2024 General Election, the challenges of democracy have shifted from technical management to the prevention of polarization, money politics, digital disinformation, identity politics, and echo chambers. This article analyzes the urgency of implementing sustainable voter education during the inter-election period, using the General Election Commission (KPU) of Balikpapan City as a case study. The study focuses on KPU Balikpapan’s strategies to transform pragmatic voters, who are susceptible to manipulation, into informed participants, while also addressing the vulnerabilities of first-time voters ahead of the 2029 Election to increase participation rates. The analysis indicates that political education during the non-election period is a critical moment to build the cognitive foundation of voters without compromising their independent choice, making the role of KPU Balikpapan essential in maintaining democratic integrity in the city.